Understanding Oracle APEX 5 Application Development - Sciore, Edward (Springer eBooks, 2015)
This new edition of Understanding Oracle APEX 5 Application Development shows APEX developers how to build practical, non-trivial web applications. The book introduces the world of APEX properties, explaining the functionality supported by each page component as well as the techniques developers use to achieve that functionality. The book is targeted at those who are new to APEX and just beginning to develop real projects for production deployment. Reading the book and working the examples will leave you in a good position to build good-looking, highly-functional, web applications. Topics include: conditional formatting, user-customized reports, data entry forms, concurrency and lost updates, and updatable reports. Accompanying the book is a demo web application that illustrates each concept mentioned in the book. Specific attention is given in the book to the thought process involved in choosing and assembling APEX components and features to deliver a specific result. Understanding Oracle APEX 5 Application Development is the ideal book to take you from an understanding of the individual pieces of APEX to an understanding of how those pieces are assembled into polished applications. Teaches how to develop non-trivial APEX applications. Provides deep understanding of APEX functionality. Shows the techniques needed for customization.